Effect of Conception Vessel Moxibustion of Different Duration on Urinary Function in Patients with Neurogenic Bladder after Suprasacral Spinal Cord Injury - Jun LENG; Wen GUO; Huimin LIU; Xiaoxue LENG; Xiaolei FANG; Chen ZHANG (康复学报)
Objective:To observe the effect of conception vessel moxibustion of different duration on urinary function in patients with neurogenic bladder (NB) after suprasacral spinal cord injury (SSCI).Methods:A total of 60 patients with NB after SSCI in the second affiliated Hospital of Shandong University of Traditional Chinese Medicine from December 2016 to December 2018, which were randomly divided into the control group and the observation group, with 30 cases in each group. The control group was given conception vessel moxibustion at conception vessel segment[Jiuwei (RN 15) to Zhongji (RN 3)], moxibustion for one hour each time, three times a week, continuous treatment for four weeks. The observation group moxibustion for two hours each time, and the other treatment procedures were the same as those in the control group, three times a week, continuous treatment for four weeks. Before treatment and after treatment for four weeks, the bladder urination function was evaluated by 24-hour urination diary (single urination volume, 24-hour urination frequency, 24-hour leakage frequency), maximum safe bladder capacity and residual urine volume.Results:After treatment for four weeks, the number of urination, the number of leaks, single urination volume, maximum safe bladder capacity and residual urine volume in the control group were (11.25±0.43) times/day, (5.30±0.37) times/day, and (148.55±17.81) mL/time, (301.90±14.73) mL, (72.50±7.21) mL, respectively. While the observation group were (9.80±1.51) times/day, (4.45±0.31) times/day, (159.40±10.97) mL, (314.90±16.33) mL, (67.05±7.18) mL, respectively. Compared with before treatment, 24-hour urination frequency, 24-hour leakage frequency and residual urine volume of the two groups after treatment for four weeks were significantly decreased, single urination volume and maximum safe bladder capacity of the two groups were significantly improved (P< 0.05). Compared with the control group, 24-hour urination frequency, 24-hour leakage frequency and residual urine volume of the observation group decreased more significantly, single urination volume and maximum safe bladder capacity of the observation group improved more significantly (P< 0.05).Conclusion:Long-term conception vessel moxibustion can effectively improve the urination function and reduce urinary incontinence in patients with neurogenic bladder after SSCI.